Religious Teachings as the Key to Social Peace and Harmony: An Approach from an Islamic Point of View - Asra Aslam; Rafique Anjum; Bilal Ahmad Dar (al-Afkar, Journal For Islamic Studies, 2023)
"Islam" is derived from the Arabic root "Salema," which implies peace, submission, purity, and obedience. Islam is frequently regarded as a religion that prioritizes the use of violence in its missionary efforts. A body of literature and media depicting Islam as a violent faith has contributed to the stereotype. The Qur’an, the major source of Islamic teaching, depicts a human as being both eager to collaborate and prone to dispute, with a preference for conflict resolution through peaceful means. In the Qur’an,ic worldview, the three levels of peace are conceptualized using three terms: as-silmu, as-shulhu, and al-amanu. The purpose of this article is to investigate how the Qur’an, encourages Muslims to engage in religious tolerance and harmony with people of other religions in order to bring about a true manifestation of peace and brotherhood in diversity, as well as respect for each other's rights as places of worship based on their common humanity. As a result, the study describes the Qur’an,ic principles, hadith, and opinions of other scholars for maintaining religious harmony and peaceful coexistence among societies, such as human equality, mutual understanding, tolerance, dispute resolution, cooperation, and religious and intellectual freedom. This report also emphasises the function of educational groups in raising public knowledge about the importance of maintaining societal peace and harmony.